2012
DOI: 10.1007/s12195-012-0253-8
|View full text |Cite
|
Sign up to set email alerts
|

Role of Epidermal Growth Factor-Triggered PI3K/Akt Signaling in the Migration of Medulloblastoma-Derived Cells

Abstract: Medulloblastoma (MB) is the most common brain cancer diagnosed among children. The cellular pathways that regulate MB invasion in response to environmental cues remain incompletely understood. Herein, we examine the migratory response of human MB-derived Daoy cells to different concentration profiles of Epidermal Growth Factor (EGF) using a microfluidic system. Our findings provide the first quantitative evidence that EGF concentration gradients modulate the chemotaxis of MB-derived cells in a dose-dependent m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 38 publications
2
47
0
Order By: Relevance
“…MAPKs are a superfamily of protein serine–threonine kinases including ERKs. In addition, previous study found that EGF-induced receptor phosphorylation triggered the activation of downstream PI3K/Akt pathway which resulted in the change of various biological effects [41], [42]. To further clarify the potential mechanisms in the SH3GL2-dependent regulation of malignant behavior of GSCs, the detection of ERK and PI3K/AKT activity was carried out by Western blot after the expression of miR-330 and SH3GL2 were changed.…”
Section: Discussionmentioning
confidence: 99%
“…MAPKs are a superfamily of protein serine–threonine kinases including ERKs. In addition, previous study found that EGF-induced receptor phosphorylation triggered the activation of downstream PI3K/Akt pathway which resulted in the change of various biological effects [41], [42]. To further clarify the potential mechanisms in the SH3GL2-dependent regulation of malignant behavior of GSCs, the detection of ERK and PI3K/AKT activity was carried out by Western blot after the expression of miR-330 and SH3GL2 were changed.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments used our established microfluidic system, called the bridged μLane, whose design and operation has been described previously in greater detail (Able et al, 2012; Dudu et al, 2012; Kong et al, 2010; Rico-Varela et al, 2015). As shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The simulation revealed that the concentration distribution within the microchannel reached steady-state at t = 103 h, after which no changes in concentration with time were seen. Concentration gradients were obtained by calculating the change in concentration along the channel length as done previously 15 via Eq. (3): G=Cx where G is gradient, C is concentration (ng/mL), and x (m) is distance.…”
Section: Methodsmentioning
confidence: 99%